Biochemical and structural studies of ASPP proteins reveal differential binding to p53, p63, and p73. - Robinson, R; Lu, X; Jones, E; Siebold, C (2008)
ASPP1 and ASPP2 are activators of p53-dependent apoptosis, whereas iASPP is an inhibitor of p53. Binding assays showed differential binding for C-terminal domains of iASPP and ASPP2 to the core domains of p53 family members p53, p63, and p73. We also determined a high-resolution crystal structure for the C terminus of iASPP, comprised of four ankyrin repeats and an SH3 domain. The crystal lattice revealed an interaction between eight sequential residues in one iASPP molecule and the p53-binding site of a neighboring molecule. ITC confirmed that a peptide corresponding to the crystallographic interaction shows specific binding to iASPP. The contributions of ankyrin repeat residues, in addition to those of the SH3 domain, generate distinctive architecture at the p53-binding site suitable for inhibition by small molecules. These results suggest that the binding properties of iASPP render it a target for antitumor therapeutics and provide a peptide-based template for compound design.